Investigating Listening to English Pop Song in Augmenting Vocabulary Mastery: A Case Study of Indonesian Undergraduate Students' Views - Jabarul Akbar Khairul Amien; Nikken Anugerahing Prasetyo; Rina Husnaini Febriyanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Mastering vocabulary is one of the difficulties for EFL learners in learning English due to various factors such as diverse cultures, language constructions, and learning motivation. Thus, elevating vocabulary needs promising activities such as listening to English pop songs. This study investigates listening to English pop songs to augment vocabulary mastery in Indonesian undergraduate students’ views. This study used a descriptive qualitative study as the research design. The participants of this study were 20 university students from diverse public and private universities with distinct majors in Jakarta, Indonesia. The research instruments in this study employed the questionnaire and interview. The results of this research indicate that listening to English pop songs promotes potential activity for the participants in augmenting their vocabulary mastery and other skills.